The equation 2x^3 + 9x^2 -18x = 0 has to be solved.

2x^3 + 9x^2 -18x = 0

=> x*(2x^2 + 9x - 18) = 0

=> x*(2x^2 + 12x - 3x - 18) = 0

=> x*(2x(x + 6) - 3(x + 6)) = 0

=> x*(2x-3)(x + 6)...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The equation 2x^3 + 9x^2 -18x = 0 has to be solved.

2x^3 + 9x^2 -18x = 0

=> x*(2x^2 + 9x - 18) = 0

=> x*(2x^2 + 12x - 3x - 18) = 0

=> x*(2x(x + 6) - 3(x + 6)) = 0

=> x*(2x-3)(x + 6) = 0

This gives x = 0

2x - 3 = 0

=> x = 3/2

x + 6 = 0

=> x = -6

**The solutions of the equation are {-6, 0, 3/2}**